2013
DOI: 10.1136/annrheumdis-2013-203832
|View full text |Cite
|
Sign up to set email alerts
|

The histamine H4 receptor mediates inflammation and Th17 responses in preclinical models of arthritis

Abstract: ObjectiveThe histamine H4 receptor (H4R) has been shown to drive inflammatory responses in models of asthma, colitis and dermatitis, and in these models it appears to affect both innate and adaptive immune responses. In this study, we used both H4R-deficient mice and a specific H4R antagonist, JNJ 28307474, to investigate the involvement of the H4R in mouse arthritis models.MethodsH4R-deficient mice and wild-type mice administered the H4R antagonist were studied in models of collagen antibody-induced arthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 35 publications
2
52
0
2
Order By: Relevance
“…Furthermore, it was shown that Th17 cell development in vivo was inhibited in H 4 R-deficient mice or mice treated with an H 4 receptor antagonist . Finally, a reduction in IL-17 levels via H 4 receptor blockade has been noted in mouse models of asthma, dermatitis, and arthritis (Dunford et al, 2006;Cowden et al, 2010bCowden et al, , 2014. Basophils have been implicated in enhancing Th17 responses in humans, and this effect appears to be mediated by H 2 receptor and H 4 receptor (Wakahara et al, 2012).…”
Section: Functionmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, it was shown that Th17 cell development in vivo was inhibited in H 4 R-deficient mice or mice treated with an H 4 receptor antagonist . Finally, a reduction in IL-17 levels via H 4 receptor blockade has been noted in mouse models of asthma, dermatitis, and arthritis (Dunford et al, 2006;Cowden et al, 2010bCowden et al, , 2014. Basophils have been implicated in enhancing Th17 responses in humans, and this effect appears to be mediated by H 2 receptor and H 4 receptor (Wakahara et al, 2012).…”
Section: Functionmentioning
confidence: 98%
“…Expression coupled with function defined by pharmacological methods has been shown on mast cells; eosinophils; neutrophils; dendritic cells; Langerhans cells; natural killer cells; monocytes; T cells, including gdT cells, T helper 1, 2, and 17 cells; keratinocytes; inflammatory dendritic epidermal cells; and fibroblasts (Gantner et al, 2002;Hofstra et al, 2003;Ling et al, 2004;Lippert et al, 2004;Gutzmer et al, 2005Gutzmer et al, , 2009Sander et al, 2006;Damaj et al, 2007;Dijkstra et al, 2007Dijkstra et al, , 2008Godot et al, 2007;Bäumer et al, 2008;Ikawa et al, 2008;Yamaura et al, 2009;Gschwandtner et al, 2010Gschwandtner et al, , 2011Gschwandtner et al, , 2012Gschwandtner et al, , 2013Truta-Feles et al, 2010;Mommert et al, 2012;Glatzer et al, 2013;Mirzahosseini et al, 2013;Cowden et al, 2014;Czerner et al, 2014;Dib et al, 2014;Jemima et al, 2014). In addition, expression data, but as to date no functional data, have been reported in epithelial cells and basophils (Hofstra et al, 2003;Sander et al, 2006).…”
Section: Anatomic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…their efforts to search for safer drugs representing the same effect or even less potencies but with less adverse effects. Histaminic receptors especially H1 3,20 and H4 [21][22][23] receptors have been shown to interfere with pain and inflammation. Therefore it can be deducted that their antagonists could possibly inhibit pain and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Пока остались на уровне лабораторных разработок перспективный ингибитор фактора активации тромбоци-тов исрапафант [76] и серия антигистаминных препара-тов нового поколения, способных блокировать Н4-ре-цепторы [77,78]. Продолжаются клинические испытания синтетических препаратов, способных блокировать ре-цептор кальцитонин-ген-связанного пептида (КГСП) -телкагепанта и олсегепанта, а также мАТ против молеку-лы КГСП и его мембранного рецептора.…”
Section: медленно действующие противовоспалитель-ные средства («хондрunclassified